ANALISIS GAYA BAHASA DALAM NOVEL MALAM UNTUK SOE HOK GIE KARYA HERLINATIENS - Desinta, Cecillia Cris; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrack: The purpose in research is describe and interpret figure of speech comparison, satire, affirmation, opposition, and describe the implementation style in learning Indonesian language in high school using Malam untuk Soe Hok Gie novel by Herlinatiens. The method in research is descriptive qualitative terms. The approach used is stylistic. The style of language comparison there are 15 figure of speech. This style of language compare a thing by the other thing. The style of language satire there are 4 figure of speech. This style of language reveal to someone or policy. The style of language affirmation there are 17 figure of speech. This style of language reveal the idea with repeat word aims to convince the reader. The style of language contention there are 4 figure of speech. This style of language reveal two things that contrary, but correct because based on to the fact. The results of this study expected usable by teacher to teaching materials for students analyze the style of language comparison, allusions, affirmation, and contention.Â Keywords: The Style of Language, Novel, Stylistic